Self-Perceived Physical Level and Fitness Performance in Children and Adolescents with Inflammatory Bowel Disease - Francesca Penagini; Valeria Calcaterra; Dario Dilillo; Matteo Vandoni; Laura Gianolio; Alessandro Gatti; Giulia Rendo; Matteo Giuriato; Lucia Cococcioni; Annalisa De Silvestri; Gianvincenzo Zuccotti (MDPI AG, 2022)
Background: Inflammatory bowel disease (IBD) patients show a higher risk of developing metabolic and cardiovascular diseases due to the presence of systemic low-grade chronic inflammation. Exercise can improve cardiovascular fitness and modulate the inflammatory processes. We evaluated the physical activity (PA) level and the fitness performance of children and adolescents with IBD. Patients and methods: We considered 54 pediatric patients with IBD (14.6 ± 2.2; 22 M), including CD (n = 27) UC (n = 24) and IBD unclassified (n = 3), and 70 healthy children. In all children, the Physical Activity Questionnaire (PAQ-C) and the International Fitness Enjoyment Scale were self-reported and recorded. Results: PAQ-C showed significant difference in PA levels in patients with IBD compared to controls (p < 0.001). A decrease in general fitness (p = 0.003), cardiorespiratory fitness (p = 0.002), strength (p = 0.01), speed agility (p = 0.003), and flexibility (p = 0.01) were also detected between patients and controls. Speed agility was related to age (p = 0.02) and BMI z-score (p = 0.01), and flexibility to BMI z-score (p = 0.05). We noted a correlation between PA levels and physician global assessment (p = 0.021) and activity disease severity (p = 0.025). Conclusions: A poorer PA level and poor physical competence were found in patients with IBD compared to healthy children and adolescents. Monitored exercise could provide multiple benefits at both physical and psychological levels.